A critical role for ceramide synthase 2 in liver homeostasis: I. alterations in lipid metabolic pathways - Pewzner-Jung, Yael; Park, Hyejung; Laviad, Elad L.; Silva, Liana C.; Lahiri, Sujoy; Stiban, Johnny; Erez-Roman, Racheli; Brügger, Britta; Sachsenheimer, Timo; Wieland, Felix T.; Prieto, Manuel; Merrill, Alfred H.; et al. (The journal of biological chemistry, 2010)
Ceramide is an important lipid signaling molecule that plays critical roles in regulating cell behavior. Ceramide synthesis is surprisingly complex and is orchestrated by six mammalian ceramide synthases, each of which produces ceramides with restricted acyl chain lengths. We have generated a CerS2 null mouse and characterized the changes in the long chain base and sphingolipid composition of livers from these mice. Ceramide and downstream sphingolipids were devoid of very long (C22-C24) acyl chains, consistent with the substrate specificity of CerS2 toward acyl-CoAs. Unexpectedly, C16-ceramide levels were elevated, and as a result, total ceramide levels were unaltered; however, C16-ceramide synthesis in vitro was not increased. Levels of sphinganine were also significantly elevated, by up to 50-fold, reminiscent of the effect of the ceramide synthase inhibitor, fumonisin B1. With the exceptions of glucosylceramide synthase and neutral sphingomyelinase 2, none of the other enzymes tested in either the sphingolipid biosynthetic or degradative pathways were significantly changed. Total glycerophospholipid and cholesterol levels were unaltered, although there was a marked elevation in C18:1 and C18:2 fatty acids in phosphatidylethanolamine, concomitant with a reduction in C18:0 and C20:4 fatty acids. Finally, differences were observed in the biophysical properties of lipid extracts isolated from liver microsomes, with membranes from CerS2 null mice displaying higher membrane fluidity and showing morphological changes. Together, these results demonstrate novel modes of cross-talk and regulation between the various branches of lipid metabolic pathways upon inhibition of very long acyl chain ceramide synthesis.